THE POLITICS OF THE PLATE: CASTE AND CONSUMPTION IN JOOTHAN - Pradhan, Priyadarsini; Das, Pranati; Sahoo, Sudarsan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Omprakash Valmiki’s autobiography, Joothan: A Dalit’s Life, stands as a seminal work in Dalit literature, offering an unflinching testimony to the brutalities of caste oppression in post-independence India. This paper argues that in Joothan, the consumption of ritually polluted, leftover food—the eponymous joothan—is not merely an indicator of poverty but a central and systemic mechanism of caste-based violence, humiliation, and the dehumanization of Dalits. The narrative meticulously demonstrates how food and commensality operate as a primary site for the performance of upper-caste power and the enforcement of a rigid social hierarchy. Drawing upon an analytical framework that combines the sociology of food, caste studies, and theories of purity and pollution, this paper examines the material and symbolic weight of joothan. It first establishes the theoretical underpinnings of food-based caste rules before analyzing how the forced consumption of waste functions as a tool of subjugation, inflicting deep psychological trauma. Conversely, the paper explores how acts of refusal—rejecting the polluted scraps—and the autonomous preparation of food become pivotal moments of resistance and the reclamation of Dalit dignity. By tracing this politics of the plate, the paper highlights Joothan's profound contribution to understanding the visceral, everyday experience of structural violence and the complex process of forging a resistant Dalit identity in the face of systemic degradation. The analysis concludes by connecting Valmiki's narrative to the persistence of food-based discrimination in contemporary India, affirming the text's enduring relevance.